In-vitro assessment of the effects of fibrinogen, recombinant factor VIIa and factor XIII on trauma-induced coagulopathy. Issue 4 (June 2020) - Budnik, Ivan; Shenkman, Boris; Morozova, Olga; Einav, Yulia
Abstract : N/A: Trauma-induced coagulopathy (TIC) occurs commonly as a second event following severe injury. We evaluated the effects of fibrinogen, recombinant factor VIIa and factor XIII on blood clotting and fibrinolysis in an in-vitro TIC model. The TIC model included hemodilution, hyperfibrinolysis, acidosis and hypothermia. The extent of clot formation and fibrinolysis was evaluated using rotational thromboelastometry. Clot strength was increased following spiking the TIC blood with either 1.0 mg/ml fibrinogen, 3.0 μg/ml recombinant factor VIIa or 2.0 IU/ml factor XIII. Maximal effect was achieved by all agents in combination approximating the extent of clot formation to those in normal blood. Fibrinolysis was inhibited by factor XIII, while the reduction was stronger using all agents together. When each of the agents used in two times lower concentrations, clot strength was near to threshold. Fibrinogen and factor XIII but not factor VIIa exerted stimulation of clot strength, whereas synergistic effect of fibrinogen and factor XIII was observed. Maximal effect was achieved combining all agents. The antifibrinolytic effect was observed only by co-administration of fibrinogen, factor XIII and factor VIIa. On the basis of our study, we suggest that stimulation of clot formation and inhibition of fibrinolysis may be achieved by combination of FG, rFVIIa an FXIII using each of them at minimal effective concentration. Taken into consideration, multifactorial TIC pathogenesis, this approach may be preferable for improving coagulopathy than separate blood spiking with the essayed factors at high concentrations.